Does bringing an action manifestly unfounded within the meaning of Article 191(1) of the Code of Civil Procedure interrupt the limitation period? - Tomczak, Tomasz (Studia Iuridica Toruniensia, 2021)
By the Act of 4 July 2019 amending the Act – Code of Civil Procedure and certain other acts, the legislator introduced to the Polish civil procedure, inter alia, the institution of dismissal of the claim as manifestly unfounded (Article 191(1) of the Polish Civil Procedure Code). The purpose of this paper is to try to answer the question: does the bringing of an action manifestly unfounded within the meaning of Article 1911 of the Code of Civil Procedure interrupt the limitation period? The considerations in the article lead to the conclusion that the answer to such a question shall be negative.